Multilayer capacitor

JP2025031538APending Publication Date: 2025-03-07SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024096782
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-23
Filing Date
2024-06-14
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0028】 一実施形態による積層型キャパシタによれば、電圧印加時に電子及びイオンキャリア(Carrier)の移動を抑制することによって絶縁抵抗の劣化を防止して信頼性が改善された積層型キャパシタを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031538000001_ABST
    Figure 2025031538000001_ABST
Patent Text Reader

Abstract

To provide a capacitor with improved reliability by suppressing migration of electrons and ion carriers upon voltage application to prevent degradation of insulation resistance.SOLUTION: A multilayer capacitor includes a capacitor body that includes a dielectric layer and an internal electrode, and an external electrode that is disposed on the outside of the capacitor body. The dielectric layer contains a plurality of dielectric crystal grains 1111 each containing a major component and a minor component. At least one or more of the dielectric crystal grains have a core-shell structure including a core 1111a, a shell 1111b, and a core-shell wall 1111c positioned between the core and the shell, and between at least two or more of dielectric crystal grains of the plurality of dielectric crystal grains, a crystal grain boundary is included. When the average concentration of the minor component in the crystal grain boundary is denoted by CGB (at %) and the average concentration of the minor component in the core-shell wall is denoted by CCS (at %), CCS / CGB is in a range from 0.40 to 0.75.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This description relates to stacked capacitors. [Background technology]

[0002] Recently, as electronic devices have rapidly become more multifunctional and smaller, electronic components have also rapidly become smaller and their performance has improved. In addition, there has been a significant increase in the demand for high reliability of electronic components for use in electrical devices such as automobiles and network facilities, and for industrial applications.

[0003] To meet these market demands, the race to develop technology for manual components such as inductors, capacitors, and resistors is accelerating. In particular, there is a need for a lot of effort to dominate the market by developing various products for multilayer ceramic capacitors (MLCCs), which are manual components and the usage and volume of which is constantly increasing.

[0004] In addition, a multilayer capacitor is a storage device manufactured by stacking dielectric layers and internal electrodes, and is used in various electronic devices such as mobile phones, notebook computers, LCD TVs, etc. In particular, as the demand for vehicles increases due to the development of electronic control technology for automobiles, and electronic devices for automobiles become smaller and more functional, there is a demand for multilayer capacitors with high temperature and moisture resistance.

[0005] In general, the reliability of a multilayer capacitor is ensured by increasing the fraction of dielectric grain boundaries in a dielectric layer to ensure insulation resistance. However, there is a limit to how much the fraction of grain boundaries can be increased to reduce the thickness and increase the capacitance of a capacitor. Summary of the Invention [Problem to be solved by the invention]

[0006] An embodiment provides a capacitor with improved reliability by preventing degradation of insulation resistance by suppressing movement of electron and ion carriers when a voltage is applied. [Means for solving the problem]

[0007] According to an embodiment, a multilayer capacitor includes a capacitor body including a dielectric layer and an internal electrode, and an external electrode disposed on an outer side of the capacitor body, the dielectric layer includes a plurality of dielectric crystal grains including a main component and a subcomponent, at least one of the plurality of dielectric crystal grains has a core-shell structure including a core; a shell; and a core-shell wall located between the core and the shell, and includes a grain boundary between at least two of the dielectric crystal grains, and an average concentration of the subcomponent at the grain boundary is C GB (at%), the average concentration of the minor component in the core-shell wall is C CS (at%), C CS / C GB satisfies 0.40 or more and 0.75 or less.

[0008] The ratio of the average diameter of the dielectric crystal grains to the average diameter of the core may be 1.2 or more and 1.8 or less.

[0009] The ratio of the average number of dielectric crystal grains including the core-shell walls to the average number of the dielectric crystal grains may be 70% or more.

[0010] The average diameter of the dielectric crystal grains may be 120 nm or more and 200 nm or less.

[0011] The average diameter of the core may be 100 nm or more and 150 nm or less.

[0012] The dielectric layer may have an average thickness of 0.05 μm or more and 0.5 μm or less.

[0013] The internal electrodes may have an average thickness of 0.05 μm or more and 0.5 μm or less.

[0014] The main components can include BaTiO3, Ba(Ti,Zr)O3, Ba(Ti,Sn)O3, (Ba,Ca)TiO3, (Ba,Ca)(Ti,Zr)O3, (Ba,Ca)(Ti,Sn)O3, (Ba,Sr)TiO3, (Ba,Sr)(Ti,Zr)O3, (Ba,Sr)(Ti,Sn)O3, or combinations thereof.

[0015] The minor components may include dysprosium (Dy), vanadium (V), manganese (Mn), chromium (Cr), silicon (Si), aluminum (Al), magnesium (Mg), tin (Sn), antimony (Sb), germanium (Ge), gallium (Ga), indium (In), barium (Ba), or combinations thereof.

[0016] The core-shell wall may contain more than 2.0 and up to 30.0 molar parts of the minor component per 100 molar parts of the major component.

[0017] The shell may contain more than 0.1 and 30.0 molar parts or less of the minor component per 100 molar parts of the major component, and the core may contain 0.1 molar parts or less of the minor component per 100 molar parts of the major component.

[0018] According to another embodiment, there is provided a multilayer capacitor including a capacitor body including a dielectric layer and an internal electrode, and an external electrode disposed on an outer side of the capacitor body, the dielectric layer including a plurality of dielectric crystal grains including a main component and a subcomponent, at least one of the plurality of dielectric crystal grains having a core-shell structure including a core; a shell; and a core-shell wall located between the core and the shell, at least two of the dielectric crystal grains including a grain boundary, and an average concentration of the subcomponent at the grain boundary is C GB (at%), the average concentration of the minor component in the core-shell wall is C CS(at%), C CS / C GB satisfies 0.40 or more and 0.75 or less, and the ratio of the average diameter of the dielectric crystal grains to the average diameter of the core is 1.2 or more and 1.8 or less.

[0019] The ratio of the average number of dielectric crystal grains including the core-shell walls to the average number of the dielectric crystal grains may be 70% or more.

[0020] The average diameter of the dielectric crystal grains may be 120 nm or more and 200 nm or less.

[0021] The average diameter of the core may be 100 nm or more and 150 nm or less.

[0022] The dielectric layer may have an average thickness of 0.05 μm or more and 0.5 μm or less.

[0023] The internal electrodes may have an average thickness of 0.05 μm or more and 0.5 μm or less.

[0024] The main components can include BaTiO3, Ba(Ti,Zr)O3, Ba(Ti,Sn)O3, (Ba,Ca)TiO3, (Ba,Ca)(Ti,Zr)O3, (Ba,Ca)(Ti,Sn)O3, (Ba,Sr)TiO3, (Ba,Sr)(Ti,Zr)O3, (Ba,Sr)(Ti,Sn)O3, or combinations thereof.

[0025] The minor components may include dysprosium (Dy), vanadium (V), manganese (Mn), chromium (Cr), silicon (Si), aluminum (Al), magnesium (Mg), tin (Sn), antimony (Sb), germanium (Ge), gallium (Ga), indium (In), barium (Ba), or combinations thereof.

[0026] The core-shell wall may contain more than 2.0 and up to 30.0 molar parts of the minor component per 100 molar parts of the major component.

[0027] The shell may contain more than 0.1 and 30.0 molar parts or less of the minor component per 100 molar parts of the major component, and the core may contain 0.1 molar parts or less of the minor component per 100 molar parts of the major component. Effect of the Invention

[0028] According to an embodiment of the multilayer capacitor, the movement of electron and ion carriers is suppressed when a voltage is applied, thereby preventing deterioration of insulation resistance and providing a multilayer capacitor with improved reliability. [Brief description of the drawings]

[0029] [Figure 1] 1 is a perspective view showing a multilayer capacitor according to an embodiment; [Diagram 2] 2 is a cross-sectional view of the multilayer capacitor taken along line II' in FIG. [Diagram 3] 2 is an exploded perspective view showing a laminated structure of internal electrode layers in the capacitor body of FIG. 1. [Figure 4] 2 is a diagram illustrating a schematic configuration of dielectric crystal grains in a dielectric layer. FIG. [Diagram 5] 1 is a transmission electron microscope (TEM) photograph of a dielectric crystal grain and a graph showing the results of measuring the dysprosium (Dy) content at each position in the dielectric crystal grain by energy dispersive X-ray analysis (EDX). [Figure 6] 1 is a scanning electron microscope image obtained by observing dielectric crystal grains in a dielectric layer with a scanning electron microscope (SEM). [Figure 7] FIG. 7 is an image showing the core-shell walls contained in the dielectric crystal grains. [Figure 8] FIG. 2 is a schematic diagram of a cross-sectional portion of a stacked capacitor including dielectric grains with core-shell walls. [Figure 9] 1 is a TEM photograph showing a line profile of a grain boundary. [Figure 10]10 is a graph showing calculation of the thickness of a grain boundary according to a contrast difference observed in the line profile of FIG. 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, the embodiments of the present invention will be described in detail with reference to the attached drawings so that a person having ordinary skill in the art to which the present invention pertains can easily carry out the present invention. In the drawings, parts that are unnecessary for the explanation are omitted in order to clearly explain the present invention, and the same or similar components are given the same reference numerals throughout the specification. In addition, the attached drawings are merely for the purpose of making it easy to understand the embodiments disclosed in the present specification, and the technical ideas disclosed in the present specification are not limited by the attached drawings, and it should be understood that the drawings include all modifications, equivalents, and alternatives included in the ideas and technical scope of the present invention.

[0031] Terms including ordinal numbers such as first, second, etc. may be used to describe various components, but the components are not limited by the terms. The terms are used only to distinguish one component from another.

[0032] When a component is said to be "coupled" or "connected" to another component, it should be understood that it may be directly coupled, connected, or facing the other component, but there may be other components in between. Conversely, when a component is said to be "directly coupled" or "directly connected" to another component, it should be understood that there are no other components in between.

[0033] Throughout the specification, the terms "comprise" or "have" and the like are intended to specify the presence of any feature, number, step, operation, component, part, or combination thereof described in the specification, but should be understood not to preclude the presence or additional possibility of one or more other features, number, step, operation, component, part, or combination thereof. Thus, when a part is said to "comprise" a certain element, this means that it can further include other elements, but not to the exclusion of other elements, unless specifically stated to the contrary.

[0034] FIG. 1 is a perspective view showing a multilayer capacitor 100 according to one embodiment, FIG. 2 is a cross-sectional view of the multilayer capacitor 100 cut along line II' in FIG. 1, and FIG. 3 is an exploded perspective view showing the stacked structure of internal electrodes in the capacitor body 110 of FIG. 1.

[0035] To clearly explain the present embodiment, the L-axis, W-axis, and T-axis shown in the drawings respectively indicate the length direction, width direction, and thickness direction of the capacitor body 110. Here, the thickness direction (T-axis direction) may be a direction perpendicular to the wide surface (main surface) of the sheet-shaped component, and may be used as the same concept as the lamination direction in which the dielectric layers 111 are laminated, for example. The length direction (L-axis direction) may be a direction extending parallel to the wide surface (main surface) of the sheet-shaped component and approximately perpendicular to the thickness direction (T-axis direction), and may be a direction in which the first external electrode 131 and the second external electrode 132 are located on both sides, for example. The width direction (W-axis direction) may be a direction extending parallel to the wide surface (main surface) of the sheet-shaped component and approximately perpendicular to the thickness direction (T-axis direction) and the length direction (L-axis direction), and the length of the sheet-shaped component in the length direction (L-axis direction) may be longer than the length of the width direction (W-axis direction).

[0036] 1 to 3, the multilayer capacitor 100 according to the present embodiment may include a capacitor body 110, and a first external electrode 131 and a second external electrode 132 disposed on opposite ends of the capacitor body 110 in a longitudinal direction (L-axis direction).

[0037] As an example, the capacitor body 110 may have a substantially hexahedral shape.

[0038] For ease of explanation, in this embodiment, the two surfaces of the capacitor body 110 that face each other in the thickness direction (T-axis direction) are defined as the first surface and the second surface, the two surfaces connected to the first surface and the second surface and facing each other in the length direction (L-axis direction) are defined as the third surface and the fourth surface, and the two surfaces connected to the first surface and the second surface and connected to the third surface and the fourth surface and facing each other in the width direction (W-axis direction) are defined as the fifth surface and the sixth surface.

[0039] As an example, the first surface, which is the lower surface, may be the surface facing the mounting direction. Also, the first to sixth surfaces may be flat, but the present embodiment is not limited to this. For example, the first to sixth surfaces may be curved surfaces with a convex center, and the corners at the boundaries between the surfaces may be rounded.

[0040] The shape and size of the capacitor body 110 and the number of laminated dielectric layers 111 are not limited to those shown in the drawings of this embodiment.

[0041] The capacitor body 110 is formed by stacking a plurality of dielectric layers 111 in the thickness direction (T-axis direction) and then firing the same, and includes a plurality of dielectric layers 111 and first internal electrode layers 121 and second internal electrode layers 122 arranged alternately in the thickness direction (T-axis direction) between the dielectric layers 111.

[0042] At this time, the boundaries between the adjacent dielectric layers 111 of the capacitor body 110 may be integrated to such an extent that it is difficult to confirm them without using a scanning electron microscope (SEM).

[0043] The capacitor body 110 may also include an active area and a cover area 112 , 113 .

[0044] The active region is a portion that contributes to forming the capacitance of the multilayer capacitor 100. As an example, the active region may be a region where the first internal electrode layer 121 or the second internal electrode layer 122 stacked along the thickness direction (T-axis direction) overlap.

[0045] The cover regions 112 and 113 are margins in the thickness direction and can be disposed on the first and second sides of the active region in the thickness direction (T-axis direction), respectively. The cover regions 112 and 113 can be a single dielectric layer 111 or two or more dielectric layers 111 stacked on the upper and lower surfaces of the active region, respectively.

[0046] In addition, the capacitor body 110 may further include a side cover region. The side cover region is a widthwise margin and may be disposed on the fifth and sixth sides of the active region in the widthwise direction (W-axis direction). Such a side cover region may be formed by applying a conductive paste layer for forming an internal electrode layer only to a part of the surface of the dielectric green sheet when applying a conductive paste layer for forming an internal electrode layer to the surface of the dielectric green sheet, laminating dielectric green sheets not applied with a conductive paste layer on both side surfaces of the surface of the dielectric green sheet, and then firing the laminate.

[0047] The cover regions 112 and 113 and the side cover regions serve to prevent the first internal electrode layer 121 and the second internal electrode layer 122 from being damaged by physical or chemical stress.

[0048] FIG. 4 is a diagram showing a schematic configuration of the dielectric crystal grains 1111 of the dielectric layer 111. As shown in FIG.

[0049] The dielectric layer 111 includes a plurality of dielectric crystal grains 1111 .

[0050] At least two of the dielectric crystal grains 1111 include a grain boundary between them.

[0051] The dielectric crystal grains 1111 include a main component and a subcomponent.

[0052] The main component is a dielectric base material, which has a high dielectric constant and contributes to the formation of the dielectric constant of the multilayer capacitor 100.

[0053] As an example, the main component is Ba m TiO3 (0.995 ≦ m ≦ 1.010), (Ba 1-X Ca x ) m (Ti 1-y Zr y )O3 (0.995 ≦ m ≦ 1.010, 0 ≦ x ≦ 0.10, 0 < y ≦ 0.20), Ba m (Ti 1-x Zr x )O3 (0.995 ≦ m ≦ 1.010, x ≦ 0.10), (Ba 1-X Ca x ) m (Ti 1-y Sn y )O3 (0.995 ≦ m ≦ 1.010, 0 ≦ x ≦ 0.10, 0 < y ≦ 0.20), or a dielectric material containing a combination thereof may be used.

[0054] As an example, the main component can include BaTiO3, Ba(Ti, Zr)O3, Ba(Ti, Sn)O3, (Ba, Ca)TiO3, (Ba, Ca)(Ti, Zr)O3, (Ba, Ca)(Ti, Sn)O3, (Ba, Sr)TiO3, (Ba, Sr)(Ti, Zr)O3, (Ba, Sr)(Ti, Sn)O3, or a combination thereof.

[0055] As an example, the sub-components can include dysprosium (Dy), vanadium (V), manganese (Mn), chromium (Cr), silicon (Si), aluminum (Al), magnesium (Mg), tin (Sn), antimony (Sb), germanium (Ge), gallium (Ga), indium, barium (Ba), or a combination thereof.

[0056] The secondary components may further include lanthanum (La), yttrium (Y), actinium (Ac), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), hafnium (Hf), or combinations thereof.

[0057] For example, the dielectric crystal grains 1111 may contain, as subcomponents, 0.5 to 2.0 molar parts of Dy2O3, 0.1 to 0.5 molar parts of Mn3O4, 0.1 to 0.5 molar parts of V2O5, 0.2 to 1.0 molar parts of BaCO3, 1.0 to 2.0 molar parts of SiO2, 0.2 to 1.5 molar parts of MgCO3, or 0.2 to 1.0 molar parts of Al2O3, relative to 100 molar parts of the main component. In this case, it is easy to make a relative comparison with respect to the dielectric change points.

[0058] Within the dielectric crystal grains 1111, there may be portions in which the molar ratio of the minor component to the major component is different from one another. For example, at least one of the plurality of dielectric crystal grains 1111 has a core-shell structure.

[0059] A dielectric crystal grain 1111 having a core-shell structure includes within one dielectric crystal grain 1111 a dielectric core 1111 a; a shell 1111 b surrounding at least a portion of the core 1111 a; and a core-shell wall 1111 c located between the core and the shell.

[0060] The core 1111a, shell 1111b, and core-shell wall 1111c have different molar ratios of the minor component to the major component, and for example, the molar ratio of the minor component to the major component may change abruptly at the boundary between the core 1111a and shell 1111b. For example, the core-shell wall 1111c, which includes the boundary between the core 1111a and shell 1111b, may include a point where the molar ratio of the minor component to the major component is maximum.

[0061] This allows the boundary between the core 1111a and the shell 1111b to be easily distinguished, and this can be confirmed through a transmission electron microscope-energy dispersive X-ray analysis (TEM-EDX).

[0062] FIG. 5 is a transmission electron microscope (TEM) image of a dielectric crystal grain and a graph showing the results of measuring the content of dysprosium (Dy), a minor component, according to the position within the dielectric crystal grain by energy dispersive X-ray analysis (EDX).

[0063] Referring to Figure 5, when a line analysis is performed on a dielectric crystal grain 1111 of a dielectric layer 111 located at the center of an active region in a cross section cut from the center of the W-axis direction of a capacitor body 110 in the L-axis direction and the T-axis direction using an EDS (Energy Disperse X-Ray Spectrometer) set up in a Transmission Electron Microscope (TEM), the part where the total content of minor components begins to increase rapidly from the center of a core 1111a of the dielectric crystal grain 1111 in the direction of one of the grain boundaries of the dielectric crystal grain 1111 is regarded as the boundary between the core 1111a and the shell 1111b, and the core 1111a and the shell 1111b can be distinguished.

[0064] Here, the center of the core 1111a can be determined as a point where the maximum long axis of the core 1111a and the maximum short axis among the short axes perpendicular to the maximum long axis of the core 1111a meet. In addition, an EDS (Energy Disperse X-Ray Spectrometer) line analysis can be performed along the maximum long axis passing through the center of the core 1111a of the dielectric crystal grain 1111.

[0065] Alternatively, the core-shell wall 1111c including the boundary between the core 1111a and the shell 1111b or the boundary between the shell 1111b and the grain boundary can be defined by dividing the areas with light and dark differences using a method such as binarizing the transmission electron microscope image.

[0066] FIG. 6 is a scanning electron microscope image obtained by observing the dielectric crystal grains of the dielectric layer with a scanning electron microscope (SEM), FIG. 7 is an image showing a core-shell wall contained in the dielectric crystal grains in FIG. 6, and FIG. 8 is a schematic diagram showing a portion of a cross section of a multilayer capacitor including dielectric crystal grains having a core-shell wall.

[0067] The core-shell wall 1111c may include the boundary between the core 1111a and the shell 1111b, and may, for example, include the point at which the molar ratio of the minor component to the major component is maximized in the core-shell wall 1111c.

[0068] 6 and 7, the core-shell wall 1111c may correspond to a dark region within a dielectric crystal grain in a scanning electron microscope (SEM) image of the dielectric crystal grain of the dielectric layer.

[0069] The core-shell walls 1111c, like the grain boundaries, can act as a barrier that suppresses the movement of electron and ion carriers when a voltage is applied to the capacitor. The core-shell walls 1111c are in an unstable state of high energy, and can attract and suppress the movement of electron and ion carriers to reach a stable energy state, thereby preventing deterioration of insulation resistance and effectively improving the reliability of the capacitor. Therefore, when the dielectric grains 1111 include the core-shell walls 1111c, the reliability of the capacitor can be effectively improved without additionally increasing the fraction of grain boundaries in a thin-film high-capacitance dielectric layer.

[0070] The core-shell wall 1111c may be a wall located at the boundary between the core 1111a and the shell 1111b and formed by dissolving the minor component in an excessive amount. The core-shell wall 1111c can be formed by the minor component being diffused uniformly at a high concentration on the surface of the major component in the initial stage of mixing and firing the major component and the minor component. After mixing and firing so that the minor component is diffused uniformly at a high concentration on the surface of the major component, a liquid phase sintering step of the major component and the minor component and a solid phase sintering step due to grain boundary migration can be performed, thereby producing dielectric crystal grains having the core-shell wall 1111c formed on the boundary between the core 1111a and the shell 1111b.

[0071] For example, the core 1111a may contain 0.1 molar parts or less of all the minor components relative to 100 molar parts of the main component, and the shell 1111b may contain more than 0.1 molar parts and less than 30.0 molar parts, or more than 0.1 molar parts and less than 20.0 molar parts, relative to 100 molar parts of the main component. If the core 1111a contains more than 0.1 molar parts of the minor components relative to 100 molar parts of the main component, the material properties of a pure dielectric material (e.g., BaTiO3) may change, if the shell 1111b contains 0.1 molar parts or less of the minor components relative to 100 molar parts of the main component, the range of change in dielectric constant due to temperature may become large, and if it contains more than 30.0 molar parts, the initial insulation resistance may decrease.

[0072] For example, the core-shell wall 1111c may contain more than 2.0 molar parts and not more than 30.0 molar parts of the minor component relative to 100 molar parts of the main component. When the core-shell wall 1111c contains more than 2.0 molar parts and not more than 30.0 molar parts of the minor component relative to 100 molar parts of the main component, deterioration of insulation resistance can be effectively prevented.

[0073] That is, the core 1111a may have no minor components or may have only a small amount of minor components. Therefore, the core 1111a does not contain impurities and is made of only a pure main component, which generally has a higher dielectric constant than a main component doped with an impurity element. Thus, the core 1111a can play a role in maintaining the dielectric constant.

[0074] The shell 1111b contains more minor components than the core 1111a. The minor components doped in the B-site of the main component (perovskite ABO3 structure) in the shell 1111b have the effect of increasing the band gap energy at which other rare earth elements and doping elements diffuse into the dielectric crystal grains 1111. This allows the shell 1111b to act as a barrier that inhibits other rare earth elements and doping elements from diffusing into the dielectric crystal grains 1111. The shell 1111b inhibits the growth of the dielectric crystal grains 1111, thereby contributing to the fine graining of the dielectric crystal grains 1111. In addition, the minor components doped in the A-site of the main component in the shell 1111b can improve reliability and dielectric constant.

[0075] The core-shell wall 1111c contains the most minor components, and thus, like the grain boundaries, can prevent the insulation resistance from deteriorating by suppressing the movement of electron and ion carriers when a voltage is applied to the capacitor.

[0076] In the multilayer capacitor according to an embodiment, the average concentration of the minor component at the grain boundary of the dielectric crystal grains 1111 is C GB (at%), the average concentration of the minor component in the core-shell wall 1111c is C CS (at%), C CS / C GB satisfies 0.40 or more and 0.75 or less.

[0077] The average concentration C of the minor component at the grain boundary of the dielectric crystal grain 1111 GB may mean the average concentration (at%) of the minor component relative to the concentration of the major component contained in the grain boundary, and the average concentration C CS can mean the average concentration (at %) of the minor component relative to the concentration of the major component contained in the core-shell wall 1111c.

[0078] When this range is satisfied, a multilayer capacitor having excellent dielectric constant and effectively prevented deterioration of insulation resistance can be realized, thereby improving reliability.

[0079] FIG. 9 is a TEM photograph showing a line profile of a grain boundary, and FIG. 10 is a graph showing calculation of the thickness of the grain boundary according to the contrast difference observed in the line profile of FIG. 9 in order to accurately determine the grain boundary.

[0080] 9 and 10, the average concentration of the minor components at the grain boundary and the core-shell wall 1111c is measured as follows.

[0081] First, a thin film sample for observation with a transmission electron microscope (TEM) is prepared by FIB microsampling, and then the thin film sample is subjected to Ar milling to prepare a core-shell wall 1111c having a thickness of about 80 nm and a scanning transmission electron microscope (STEM) sample for observation of grain boundaries.

[0082] Thereafter, the probe diameter of the electron beam is set to about 0.5 nm or less to analyze the core-shell wall 1111c and the grain boundary, where only the core-shell wall 1111c and the grain boundary that are not inclined with respect to the incident electron beam are analyzed.

[0083] 9 and 10, as shown in the HAADF-STEM images (magnification × 2.25M) of the grain boundaries, the full width at half maximum (FWHM) of the peak observed in the line profile of the grain boundaries is measured and defined as the thickness of the grain boundaries, and the composition analysis of the grain boundaries is performed by comparative analysis with respect to regions having the same thickness.

[0084] In addition, the full width at half maximum (FWHM) of the peak seen in the line profile of the core-shell wall 1111c is measured and defined as the thickness of the core-shell wall 1111c, and the composition analysis of the core-shell wall 1111c is performed by comparative analysis with respect to an area having an equivalent thickness.

[0085] In addition, the grain boundary component analysis can be performed by irradiating an electron beam to one point on the layer and performing EDS analysis to obtain the conditions for the grain boundary without inclination and the probe diameter. At this time, measurements are performed at 20 points for each sample and the average value is calculated.

[0086] In addition, the component analysis of the core-shell wall 1111c can be obtained by irradiating an electron beam to one point of the layer and performing EDS analysis to determine the conditions for the core-shell wall 1111c without inclination and the probe diameter. At this time, measurements are performed at 20 points for each sample and the average value is calculated.

[0087] In one embodiment, the dielectric crystal grains 1111 may have an average diameter of 120 nm to 200 nm, and the cores 1111a may have an average diameter of 100 nm to 150 nm.

[0088] The ratio of the average diameter of the dielectric crystal grains 1111 to the average diameter of the cores 1111a may be 1.2 to 1.8. When this range is satisfied, a multilayer capacitor having excellent dielectric constant and effectively prevented deterioration of insulation resistance, thereby improving reliability, can be realized.

[0089] The average diameter of the dielectric crystal grains 1111 and the average diameter of the cores 1111a are measured by the following method.

[0090] As an example, the stacked capacitor 100 is immersed in an epoxy mixture and hardened, and then the sides of the L-axis and T-axis directions of the capacitor body 110 are polished to 1 / 2 the W-axis direction, and after being fixed, the capacitor body 110 is maintained in a vacuum atmosphere chamber, and cross-sectional samples are prepared by cutting the capacitor body 110 from the center of the W-axis direction in the L-axis and T-axis directions.

[0091] The cross-sectional sample is then etched using a 0.2% solution of hydrofluoric acid and a 1% solution of nitric acid for about 10 seconds to prepare a scanning electron microscope (SEM) image.

[0092] In the SEM image, an arbitrary dielectric layer 111 is selected at the center of the length direction (L-axis direction) or width direction (W-axis direction), and the diameter of the dielectric crystal grain 1111 and the diameter of the core 1111a are measured. In this case, the diameter of the dielectric crystal grain 1111 and the diameter of the core 1111a can be calculated as the average value of the maximum major axis and the maximum minor axis among the minor axes perpendicular to the maximum major axis. In addition, 500 or more dielectric crystal grains are selected in the same dielectric layer, and the diameters of the dielectric crystal grains 1111 and the core 1111a are measured and the average value is calculated.

[0093] In one embodiment, the ratio of the average number of dielectric crystal grains including the core-shell walls 1111c to the average number of the dielectric crystal grains 1111 may be 70% or more, for example 75% or more, or 80% or more.

[0094] When the ratio of the average number of dielectric crystal grains including the core-shell walls 1111c to the average number of the dielectric crystal grains 1111 is 70% or more, the core-shell walls 1111c can effectively suppress deterioration of insulation resistance by suppressing the movement of electron and ion carriers when voltage is applied.

[0095] The ratio of the average number of the dielectric crystal grains including the core-shell walls 1111c to the average number of the dielectric crystal grains 1111 can be measured by the following method.

[0096] First, an arbitrary dielectric layer 111 is selected from the scanning electron microscope (SEM) image of the cross-sectional sample, and an area of ​​1 μm x 1 μm (unit area) in the active area is measured to measure the number of dielectric crystal grains 1111 per unit area and the number of dielectric crystal grains including the core-shell wall 1111c.

[0097] As an example, when the dielectric crystal grains of the dielectric layer as shown in FIG. 6 are observed using a scanning electron microscope (SEM), a scanning electron microscope image of the dielectric crystal grains including the core-shell wall 1111c is obtained as shown in FIG. 7. Using such an image, the number of dielectric crystal grains 1111 and the number of dielectric crystal grains including the core-shell wall 1111c can be measured.

[0098] Next, the average number of dielectric crystal grains 1111 and the average number of dielectric crystal grains including core-shell walls 1111c may be the arithmetic average of three values ​​measured on three different dielectric layers 111 in the L-axis and T-axis cross sections obtained above, or may be the arithmetic average of a total of nine values ​​measured at the center, one end, and the other end of the active area on three different dielectric layers 111 in the L-axis and T-axis cross sections above.

[0099] As an example, the average thickness of the dielectric layer 111 may be 0.05 μm or more, 0.1 μm or more, or 0.2 μm or more, and may be 0.5 μm or less, or 0.4 μm or less.

[0100] If the average thickness of the dielectric layer 1111 is less than 0.05 μm, it may be difficult to confirm the improvement in reliability.

[0101] The average thickness of the dielectric layer 111 may be an arithmetic average value of the thicknesses of the dielectric layer 111 at 10 points spaced apart from a central point in the length direction (L-axis direction) or width direction (W-axis direction) of the dielectric layer 111 in a scanning electron microscope (SEM) image of the cross-sectional sample by a predetermined distance from the central point. The distance between the 10 points may be adjusted according to the scale of the scanning electron microscope (SEM) image, and may be, for example, 1 μm to 100 μm, 1 μm to 50 μm, or 1 μm to 10 μm. In this case, all of the 10 points must be located within the dielectric layer 111. If all of the 10 points are not located within the dielectric layer 111, the position of the reference point may be changed or the distance between the 10 points may be adjusted.

[0102] The first internal electrode 121 and the second internal electrode 122 are electrodes having different polarities and are alternately arranged to face each other along the T-axis direction with the dielectric layer 111 in between, and one end of each of the electrodes can be exposed through the third and fourth surfaces of the capacitor body 110, respectively.

[0103] The first internal electrode 121 and the second internal electrode 122 can be electrically insulated from each other by the dielectric layer 111 disposed therebetween.

[0104] Ends of the first internal electrode 121 and the second internal electrode 122 alternately exposed through the third and fourth surfaces of the capacitor body 110 may be electrically connected to the first external electrode 131 and the second external electrode 132, respectively.

[0105] The first internal electrode 121 and the second internal electrode 122 include a conductive metal, and may include, for example, a metal such as Ni, Cu, Ag, Pd, or Au, or an alloy thereof, for example, an Ag-Pd alloy.

[0106] Furthermore, the first internal electrode 121 and the second internal electrode 122 may contain dielectric particles having the same composition as the ceramic material contained in the dielectric layer 111 .

[0107] The first internal electrode 121 and the second internal electrode 122 may be formed using a conductive paste containing a conductive metal. The conductive paste may be printed by screen printing or gravure printing.

[0108] For example, the average thickness of the first internal electrode 121 and the second internal electrode 122 may be 0.05 μm or more, 0.1 μm or more, 0.2 μm or more, or 0.25 μm or more, and may be 0.5 μm or less, 0.4 μm or less, or 0.37 μm or less.

[0109] The average thickness of the first internal electrode 121 or the second internal electrode 122 may be an arithmetic average value of the thicknesses of the first internal electrode 121 or the second internal electrode 122 at 10 points spaced apart from the center point in the length direction (L-axis direction) or width direction (W-axis direction) of the first internal electrode 121 or the second internal electrode 122 in a scanning electron microscope (SEM) image of the cross-sectional sample. The interval between the 10 points may be adjusted according to the scale of the scanning electron microscope (SEM) image, and may be, for example, 1 μm to 100 μm, 1 μm to 50 μm, or 1 μm to 10 μm. In this case, all of the 10 points must be located within the first internal electrode 121 or the second internal electrode 122. If all of the 10 points are not located within the first internal electrode 121 or the second internal electrode 122, the position of the reference point may be changed or the interval between the 10 points may be adjusted.

[0110] The first external electrode 131 and the second external electrode 132 are provided with voltages of different polarities and are electrically connected to the exposed portions of the first internal electrode 121 and the second internal electrode 122, respectively.

[0111] With the above-described configuration, when a predetermined voltage is applied to the first external electrode 131 and the second external electrode 132, charges are stored between the opposing first internal electrode 121 and second internal electrode 122. At this time, the capacitance of the multilayer capacitor 100 is proportional to the overlapping area of ​​the first internal electrode 121 and the second internal electrode 122 overlapping each other along the T-axis direction in the active region.

[0112] The first external electrode 131 and the second external electrode 132 may each include a first and a second connection portion arranged on the third and fourth surfaces of the capacitor body 110 and connected to the first internal electrode 121 and the second internal electrode 122, respectively, and a first and a second band portion arranged at the corner where the third and fourth surfaces of the capacitor body 110 meet the first and second surfaces or the fifth and sixth surfaces.

[0113] The first and second band portions may extend from the first and second connection portions to parts of the first and second surfaces or the fifth and sixth surfaces of the capacitor body 110. The first and second band portions may serve to improve the bonding strength between the first external electrode 131 and the second external electrode 132.

[0114] As an example, the first external electrode 131 and the second external electrode 132 may each include a sintered metal layer in contact with the capacitor body 110, a conductive resin layer arranged to cover the sintered metal layer, and a plating layer arranged to cover the conductive resin layer.

[0115] The sintered metal layer may include a conductive metal and glass.

[0116] As an example, the sintered metal layer may include copper (Cu), nickel (Ni), silver (Ag), palladium (Pd), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), lead (Pb), alloys thereof, or combinations thereof as the conductive metal, for example, copper (Cu) may include a copper (Cu) alloy. When the conductive metal includes copper, metals other than copper may be included in an amount of 5 molar parts or less relative to 100 molar parts of copper.

[0117] For example, the sintered metal layer may include a composition in which an oxide is mixed with glass, and may be at least one selected from the group consisting of silicon oxide, boron oxide, aluminum oxide, transition metal oxide, alkali metal oxide, and alkaline earth metal oxide. The transition metal may be selected from the group consisting of zinc (Zn), titanium (Ti), copper (Cu), vanadium (V), manganese (Mn), iron (Fe), and nickel (Ni), the alkali metal may be selected from the group consisting of lithium (Li), sodium (Na), and potassium (K), and the alkaline earth metal may be at least one selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba).

[0118] Alternatively, the conductive resin layer may be formed on the sintered metal layer, for example, to completely cover the sintered metal layer. Meanwhile, the first external electrode 131 and the second external electrode 132 may not include the sintered metal layer, in which case the conductive resin layer may be in direct contact with the capacitor body 110.

[0119] The conductive resin layer extends to the first and second surfaces or the fifth and sixth surfaces of the capacitor body 110, and the length of the region (i.e., band portion) where the conductive resin layer is extended to the first and second surfaces or the fifth and sixth surfaces of the capacitor body 110 may be longer than the length of the region (i.e., band portion) where the sintered metal layer is extended to the first and second surfaces or the fifth and sixth surfaces of the capacitor body 110. That is, the conductive resin layer is formed on the sintered metal layer to completely cover the sintered metal layer.

[0120] The conductive resin layer includes a resin and a conductive metal.

[0121] The resin contained in the conductive resin layer is not particularly limited as long as it has bonding and impact absorbing properties and can be mixed with the conductive metal powder to form a paste, and may include, for example, a phenolic resin, an acrylic resin, a silicone resin, an epoxy resin, or a polyimide resin.

[0122] The conductive metal contained in the conductive resin layer serves to electrically connect the first internal electrode 121 and the second internal electrode 122 or the sintered metal layer.

[0123] The conductive metal contained in the conductive resin layer may have a spherical shape, a flake shape, or a combination thereof, that is, the conductive metal may be only flake-shaped, only spherical, or a mixture of flake-shaped and spherical shapes.

[0124] Here, the spherical shape may include a shape that is not a perfect sphere, for example, a shape in which the ratio of the major axis to the minor axis (major axis / minor axis) is 1.45 or less. The flake-shaped powder means a powder having a flat and elongated shape, and is not particularly limited, and may be, for example, a ratio of the major axis to the minor axis (major axis / minor axis) of 1.95 or more.

[0125] The first external electrode 131 and the second external electrode 132 may further include a plating layer disposed on the outer side of the conductive resin layer.

[0126] The plating layer may include nickel (Ni), copper (Cu), tin (Sn), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), tungsten (W), titanium (Ti), lead (Pb), etc., alone or in combination. For example, the plating layer may be a nickel (Ni) plating layer or a tin (Sn) plating layer, or may be a layer in which a nickel (Ni) plating layer and a tin (Sn) plating layer are sequentially stacked, or a layer in which a tin (Sn) plating layer, a nickel (Ni) plating layer, and a tin (Sn) plating layer are sequentially stacked. The plating layer may also include a plurality of nickel (Ni) plating layers and / or a plurality of tin (Sn) plating layers.

[0127] The plating layer can improve the mountability of the multilayer capacitor 100 on a substrate, structural reliability, durability against the outside, heat resistance, and equivalent series resistance (ESR).

[0128] Specific examples of the present invention are presented below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and should not be construed as limiting the scope of the present invention.

[0129] [Example] (Example) The base powder is a dielectric raw material powder containing barium titanate (BaTiO3) powder with an average particle size of 100 nm as the main component, and 1.5 molar parts of Dy2O3, 0.2 molar parts of Mn3O4, 0.2 molar parts of V2O5, 0.6 molar parts of BaCO3, 1.5 molar parts of SiO2, 0.7 molar parts of MgCO3, and 0.5 molar parts of Al2O3 are added as subcomponents to 100 molar parts of the main component. A binder, an organic solvent such as ethanol / toluene, and zirconia balls are added to the mixture and wet-mixed to produce a dielectric slurry.

[0130] The prepared dielectric slurry is used in a head-discharging on-roll forming coater to prepare a dielectric green sheet having a thickness of about 0.6 μm.

[0131] A conductive paste layer containing nickel (Ni) is printed on the surface of a dielectric green sheet, and the dielectric green sheets having the conductive paste layer formed thereon are stacked and pressed to manufacture a dielectric green sheet laminate, and then the laminate is pressed and cut.

[0132] The cut laminate is then heated to remove the binder, and fired in a high-temperature reducing atmosphere to form a ceramic body. In the firing process, the laminate is fired in a reducing atmosphere (0.1% H2 / 99.9% N2, H2O / H2 / N2 atmosphere) at 1050~1250℃ for 1 hour, and then reoxidized in a nitrogen (N2) atmosphere at 1000℃ for 3 hours for heat treatment. At this time, firing is performed while controlling the average diameter of the dielectric crystal grain core and the average diameter of the dielectric crystal grain / average diameter of the core (ratio) as shown in Table 1, so that the minor component is diffused uniformly and at a high concentration to the surface of the major component in the early stage of firing.

[0133] In addition, the temperature is lowered at a fast rate during the temperature lowering process, so that the average diameter of the dielectric crystal grains in the dielectric layer is adjusted to satisfy the range of 120 nm to 200 nm.

[0134] Next, the sintered ceramic body is subjected to a termination process using copper (Cu) paste and an electrode sintering process to form external electrodes, thereby manufacturing a multilayer capacitor according to Example 1 having a dielectric layer thickness of about 0.4 μm and an internal electrode thickness of about 0.37 μm.

[0135] Multilayer capacitors of Examples 1 to 3 and Comparative Examples 1 to 6 were manufactured, differing in (1) average core diameter and (2) average dielectric crystal grain diameter / average core diameter (ratio). The results are shown in Table 1 below.

[0136] (Experimental Example) Experimental Example 1: C CS / C GB analysis First, thin film samples for transmission electron microscope observation are prepared by FIB microsampling for the stacked capacitors of Examples 1 to 3 and Comparative Examples 1 to 6. Then, the thin film samples are subjected to Ar milling to prepare scanning transmission electron microscope (STEM) samples for observing the core-shell walls and grain boundaries with a thickness of about 80 nm.

[0137] Next, the probe diameter of the electron beam is set to about 0.5 nm or less to analyze the core-shell walls and grain boundaries, and only the core-shell walls and grain boundaries that are not tilted with respect to the incident electron beam are analyzed.

[0138] 9 and 10, as shown in the HAADF-STEM images (magnification × 2.25M) of the grain boundaries, the full width at half maximum (FWHM) of the peak observed in the line profile of the grain boundaries is measured and defined as the thickness of the grain boundaries, and the composition analysis of the grain boundaries is performed by comparative analysis with respect to regions having the same thickness.

[0139] In addition, the full width at half maximum (FWHM) of the peak seen in the line profile of the core-shell wall 1111c is measured and defined as the thickness of the core-shell wall 1111c, and the composition analysis of the core-shell wall 1111c is performed by comparative analysis with respect to an area having an equivalent thickness.

[0140] In addition, the grain boundary component analysis can be performed by irradiating an electron beam to one point of the layer and performing EDS analysis to obtain the conditions for the grain boundary without inclination and the probe diameter. At this time, measurements are performed at 20 points for each sample and the average value is calculated.

[0141] In addition, the component analysis of the core-shell wall 1111c can be obtained by irradiating an electron beam to one point of the layer and performing EDS analysis to determine the conditions for the core-shell wall 1111c without inclination and the probe diameter. At this time, measurements are performed at 20 points for each sample and the average value is calculated.

[0142] This results in the average concentration of the minor component at the grain boundary, C GB (at%), the average concentration of the minor component in the core-shell wall, C CS (at%), and C CS / C GB The values ​​are shown in Table 1, item 3 below.

[0143] Experimental Example 2: Analysis of the average diameter of dielectric crystal grains / average diameter of cores (ratio) The stacked capacitors of Examples 1 to 3 and Comparative Examples 1 to 6 were placed in an epoxy mixture and cured, and then the sides of the capacitor body in the L-axis direction and T-axis direction were polished to 1 / 2 the W-axis direction. After fixing, the capacitor body was maintained in a vacuum atmosphere chamber, and cross-sectional samples were prepared by cutting the capacitor body from the center in the W-axis direction in the L-axis direction and the T-axis direction.

[0144] The cross-sectional sample is then etched using a 0.2% solution of hydrofluoric acid and a 1% solution of nitric acid for about 10 seconds to prepare a scanning electron microscope (SEM) image.

[0145] An arbitrary dielectric layer is selected at the center in the length direction (L axis direction) or width direction (W axis direction) in the SEM image, and the diameter of the dielectric crystal grain and the diameter of the core are measured.

[0146] In this case, the diameter of the dielectric crystal grain and the diameter of the core can be calculated from the average value of the maximum major axis and the maximum minor axis among the minor axes perpendicular to the maximum major axis.

[0147] In addition, 500 or more dielectric crystal grains were selected from the same dielectric layer, and the diameters of the dielectric crystal grains and the core diameters were measured to calculate the average value, which was the average diameter of the dielectric crystal grains / average core diameter (ratio) and is shown in Table 1 (2) below.

[0148] Experimental Example 3: Analysis of the ratio (%) of the average number of dielectric crystal grains including the core-shell wall For the stacked capacitors of Examples 1 to 3 and Comparative Examples 1 to 6, scanning electron microscope (SEM) images of the cross-sectional samples are prepared, an arbitrary dielectric layer is selected, and an area of ​​1 μm x 1 μm (unit area) in the active region is used as the measurement object to measure the number of dielectric crystal grains per unit area and the number of dielectric crystal grains including the core-shell wall.

[0149] Next, the number of dielectric crystal grains and the average number of dielectric crystal grains including the core-shell wall were calculated and shown in (4) of Table 1 below.

[0150] Experimental Example 4: Reliability evaluation of multilayer capacitors 400 samples were obtained for each of the capacitors in Examples 1 to 3 and Comparative Examples 1 to 6, and an evaluation was performed to see whether the reliability could be maintained for 10 hours or more without failure under conditions of 125°C and 10 V. If the reliability was maintained, it was judged as O (OK), and if the reliability was defective, it was judged as X (NG), and the results are shown in 5 of Table 1 below.

[0151] [Table 1]

[0152] Referring to Table 1, in the case of the stacked capacitors of Examples 1 to 3, C CS / C GB The value is in the range of 0.40 to 0.75, the ratio of the average diameter of the dielectric crystal grains to the average diameter of the core is 1.2 to 1.8, and the ratio of the average number of the dielectric crystal grains including the core-shell wall is 70% or more, so that it can be confirmed that the reliability of the capacitor is superior to that of the comparative example.

[0153] Although a preferred embodiment of the present invention has been described above, the present invention is not limited thereto, and can be embodied in various modified forms within the scope of the claims, the detailed description of the invention, and the attached drawings, which of course also fall within the scope of the present invention. [Explanation of symbols]

[0154] 100: Multilayer capacitor 110: Capacitor body 111: Dielectric layer 1111: Dielectric grains 1111a: Core of dielectric grain 1111b: Shell of dielectric grains 1111c: Core-shell walls of dielectric grains 112, 113: Coverage area 121: 1st internal electrode 122:Second internal electrode 131: 1st external electrode 132:Second external electrode

Claims

1. a capacitor body including a dielectric layer and an internal electrode; an external electrode disposed on an outer side of the capacitor body; the dielectric layer includes a plurality of dielectric crystal grains including a main component and a subcomponent; At least one of the plurality of dielectric crystal grains has a core-shell structure including a core; a shell; and a core-shell wall located between the core and the shell, A grain boundary is included between at least two of the dielectric crystal grains, The average concentration of the minor component at the grain boundary is C GB (at%), the average concentration of the minor component in the core-shell wall is C CS (at%), C CS / C GB A multilayer capacitor in which the value satisfies the range of 0.40 to 0.

75.

2. 2. The multilayer capacitor according to claim 1, wherein a ratio of an average diameter of said dielectric crystal grains to an average diameter of said core is 1.2 or more and 1.8 or less.

3. 2. The multilayer capacitor according to claim 1, wherein a ratio of an average number of the dielectric crystal grains including the core-shell walls to an average number of the dielectric crystal grains is 70% or more.

4. 2. The multilayer capacitor according to claim 1, wherein the average diameter of the dielectric crystal grains is 120 nm or more and 200 nm or less.

5. 2. The multilayer capacitor according to claim 1, wherein the average diameter of the core is 100 nm or more and 150 nm or less.

6. 2. The multilayer capacitor according to claim 1, wherein the average thickness of the dielectric layers is 0.05 μm or more and 0.5 μm or less.

7. 2. The multilayer capacitor according to claim 1, wherein the internal electrodes have an average thickness of 0.05 [mu]m or more and 0.5 [mu]m or less.

8. The main component is BaTiO 3 , Ba(Ti,Zr)O 3 , Ba(Ti,Sn)O 3 , (Ba, Ca)TiO 3 , (Ba, Ca) (Ti, Zr) O 3 , (Ba, Ca) (Ti, Sn) O 3 , (Ba, Sr)TiO 3 , (Ba, Sr) (Ti, Zr) O 3 , (Ba, Sr) (Ti, Sn) O 3 10. The stacked capacitor of claim 1, comprising:

9. 2. The stacked capacitor according to claim 1, wherein the minor component comprises dysprosium (Dy), vanadium (V), manganese (Mn), chromium (Cr), silicon (Si), aluminum (Al), magnesium (Mg), tin (Sn), antimony (Sb), germanium (Ge), gallium (Ga), indium (In), barium (Ba), or a combination thereof.

10. 2. The multilayer capacitor according to claim 1, wherein the core-shell wall contains more than 2.0 molar parts and not more than 30.0 molar parts of the subcomponent per 100 molar parts of the main component.

11. The shell contains more than 0.1 mol parts and not more than 30.0 mol parts of the subcomponent per 100 mol parts of the main component, 2. The multilayer capacitor according to claim 1, wherein the core contains 0.1 parts by mol or less of the subcomponent per 100 parts by mol of the main component.

12. a capacitor body including a dielectric layer and an internal electrode; an external electrode disposed on an outer side of the capacitor body; the dielectric layer includes a plurality of dielectric crystal grains including a main component and a subcomponent; At least one of the plurality of dielectric crystal grains has a core-shell structure including a core; a shell; and a core-shell wall located between the core and the shell, A grain boundary is included between at least two of the dielectric crystal grains, The average concentration of the minor component at the grain boundary is C GB (at%), the average concentration of the minor component in the core-shell wall is C CS (at%), C CS / C GB is 0.40 or more and 0.75 or less, A multilayer capacitor, wherein a ratio of an average diameter of the dielectric crystal grains to an average diameter of the core is 1.2 or more and 1.8 or less.

13. 13. The multilayer capacitor according to claim 12, wherein a ratio of an average number of the dielectric crystal grains including the core-shell walls to an average number of the dielectric crystal grains is 70% or more.

14. 13. The multilayer capacitor according to claim 12, wherein the average diameter of the dielectric crystal grains is 120 nm or more and 200 nm or less.

15. 13. The multilayer capacitor according to claim 12, wherein the average diameter of the core is 100 nm or more and 150 nm or less.

16. 13. The multilayer capacitor according to claim 12, wherein the average thickness of the dielectric layers is 0.05 μm or more and 0.5 μm or less.

17. The multilayer capacitor according to claim 12, wherein the internal electrodes have an average thickness of 0.05 μm to 0.5 μm.

18. The main component is BaTiO 3 , Ba(Ti,Zr)O 3 , Ba(Ti,Sn)O 3 , (Ba, Ca)TiO 3 , (Ba, Ca) (Ti, Zr) O 3 , (Ba, Ca) (Ti, Sn) O 3 , (Ba, Sr)TiO 3 , (Ba, Sr) (Ti, Zr) O 3 , (Ba, Sr) (Ti, Sn) O 3 13. The stacked capacitor of claim 12, comprising:

19. 13. The stacked capacitor of claim 12, wherein the minor component comprises dysprosium (Dy), vanadium (V), manganese (Mn), chromium (Cr), silicon (Si), aluminum (Al), magnesium (Mg), tin (Sn), antimony (Sb), germanium (Ge), gallium (Ga), indium (In), barium (Ba), or a combination thereof.

20. 13. The multilayer capacitor according to claim 12, wherein the core-shell wall contains more than 2.0 molar parts and not more than 30.0 molar parts of the subcomponent per 100 molar parts of the main component.

21. The shell contains more than 0.1 mol parts and not more than 30.0 mol parts of the subcomponent per 100 mol parts of the main component, 13. The multilayer capacitor according to claim 12, wherein the core contains 0.1 parts by mol or less of the subcomponent per 100 parts by mol of the main component.